Lahars in Java: Initiations, Dynamics, Hazard Assessment And Deposition Processes - Lavigne, Franck; Thouret, Jean-Claude; Hadmoko, Danang Sri; Sukatja, Bambang (Forum Geografi, 2007)
Lahar has been applied as a general term for rapidly flowing, high-concentration, poorly sorted sediment-laden mixtures of rock debris and water (other than normal streamflow) from a volcano. Lahars are one of the most destructive phenomena associated with composite volcanoes, which are dominant in Java Island. Resulting deposits of lahar are poorly sorted, massive, made up of clasts (chiefly of volcanic composition), that generally include a mud-poor matrix. The aim of this research is threefold: to discuss the initiation of lahars occurrences, their dynamics, to assess the hazard and to analyse the deposition. Lahars are either a direct result of eruptive activity or not temporally related to eruptions. Syn-eruptive lahars may result from the transformation on pyroclastic flows or debris avalanches which transform to aqueous flows (e.g. at Papandayan in November 2002); They may be also generated through lake outburst or breaching (e.g. at Kelut in 1909 or 1966), and through removal of pyroclastic debris by subsequent heavy rainstorms. Post-eruptive lahar occurs during several years after an eruption. At Merapi, lahars are commonly rain-triggered by rainfalls having an average intensity of about 40 mm in 2 hours. Most occur during the rainy season from November to April. Non-eruptive lahars are flows generated without eruptive activity, particularly in the case of a debris avalanche or a lake outburst (e.g., Kelut). A lahar may include one or more discrete flow processes and encompass a variety of rheological flow types and flow transformations. As such, lahars encompass a continuum between debris flows and hyperconcentrated flows, as observed at Merapi, Kelut and Semeru volcanoes. Debris flows, with water contents ranging from 10 to no more than about 25% weight, are non-newtonian fluids that move as fairly coherent masses in what is thought to be predominantly laminar fashion. However, the relative importance of laminar versus turbulent regime is still debatable. Hyperconcentrated streamflows contain 25- to about 40%-weight-water; these flows possess some yield stress, but they are characteristically turbulent. Hazard-zone maps for lahar were produced for most of the the Javanese volcanoes, but these maps are on too small-scale to meet modern zoning requirements. More recently, a few large-scale maps (1/10,000 and 1/2,000-scale) and risk assessments have been completed for a few critical river systems at Merapi.